Robust filters for fault detection: An LMI control setting - Ríos Bolívar, Addison; García, Germain (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Starting from the narrow relationship between robust filtering and the design of robust filters to fault detection, an approach for fault detection and diagnosis robust filter design in linear systems is presented. The method consists on transforming the problem of robust detection of faults in a problem of robust control based on Linear Matrix Inequalities (LMI). The transformation is obtained by means of the design of a dynamic system (post-filter), which is obtained through the synthesis of robust controllers based on LMl. Thus, performance index in H2, H00, and multi-objective criteria (H2, H00) can be obtained. This formulation allows the application ofany technique of robust control based on LMl's, and the robust fault detection and isolation is guaranteed